Towards the elimination of paediatric tuberculosis in high-income, immigrant-receiving countries: a 25-year conventional and molecular epidemiological case study. Issue 2 (8th May 2018) - Dhawan, Vivek; Bown, Jennifer; Lau, Angela; Langlois-Klassen, Deanne; Kunimoto, Dennis; Bhargava, Ravi; Chui, Linda; Collin, Simon M.; Long, Richard
The epidemiology of tuberculosis (TB) in high-income countries is increasingly dictated by immigration. The influence of this trend on paediatric TB and TB elimination are not well defined. We undertook a 25-year conventional and molecular epidemiologic study of paediatric TB in Alberta, one of four major immigrant-receiving provinces in Canada. All isolates of Mycobacterium tuberculosis were DNA fingerprinted using standard methodology. Between 1990 and 2014, 176 children aged 0–14 years were diagnosed with TB. Foreign-born children or Canadian-born children of foreign-born parents accounted for an increasingly large proportion of total cases during the study period (from 32.1% to 89.5%). Of the 78 culture-positive cases, 35 (44.9%) had a putative source case identified by conventional epidemiology, with 34 (97.1%) having a concordant molecular profile. Of the remaining 43 culture-positive cases, molecular profiling identified spatially and temporally related sources in six cases (14.0%). These six children, along with four other children whose source cases were discovered through reverse-contact tracing, had a high morbidity and mortality. The increasing burden of paediatric TB in both foreign-born children and Canadian-born children of foreign-born parents calls for more timely diagnosis of source cases and more targeted screening for latent TB infection. Conventional and molecular epidemiology can inform paediatric TB elimination strategy in high-income countries http://ow.ly/mwbn30iY1WF